2012
DOI: 10.2478/v10007-012-0036-8
|View full text |Cite
|
Sign up to set email alerts
|

Current status and future prospects of drug eluting stents for restenosis / Sadašnjost i budućnost stentova za restenozu koji otpuštaju lijekove

Abstract: Drug-eluting stents (DESs) prevail in the treatment of carotid artery diseases in the interventional cardiology world owing to their efficacy for significant reduction of restenosis. A current successful DES requires a polymer coating for drug delivery. Clinical trials examining several pharmaceutical agents have demonstrated marked reduction in restenosis following stenting. The development of DES is one of the major revolutions in the field of interventional cardiology. The ideal drug to prevent restenosis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The IgakiTamai scaffold had a self-expanding zigzag helical coil design, where the self-expansion of this scaffold was assisted by balloon-expansion. The obtained results of this first study in humans demonstrated a low restenosis rate and a re-intervention rate of 10.5 % at 6 months [98]. The first clinically investigated fully absorbable DES is the bioresorbable vascular scaffold (BVS) by Abbott Vascular (USA).…”
Section: Polymers For Stent Platformsmentioning
confidence: 93%
See 1 more Smart Citation
“…The IgakiTamai scaffold had a self-expanding zigzag helical coil design, where the self-expansion of this scaffold was assisted by balloon-expansion. The obtained results of this first study in humans demonstrated a low restenosis rate and a re-intervention rate of 10.5 % at 6 months [98]. The first clinically investigated fully absorbable DES is the bioresorbable vascular scaffold (BVS) by Abbott Vascular (USA).…”
Section: Polymers For Stent Platformsmentioning
confidence: 93%
“…As first Tamai et al [98] reported their clinical experiences with an absorbable coronary polymer scaffold made from PLLA, the Igaki-Tamai scaffold. The IgakiTamai scaffold had a self-expanding zigzag helical coil design, where the self-expansion of this scaffold was assisted by balloon-expansion.…”
Section: Polymers For Stent Platformsmentioning
confidence: 99%
“…Recently, biodegradable polymers (such as PLA and polylactide-co-glycolide – PLGA), and polymer-free DES were extensively studied to optimize their biocompatibility. 58 …”
Section: Instent Restenosismentioning
confidence: 99%